Sistem Kendali Kecepatan Motor pada Mobile Robot Menggunakan PID dan Analisis Disturbance Berbasis Disturbance Observer - Bayu Sandi Marta; Indra Ferdiansyah; Fernando Ardila (Jurnal Teknologi Terpadu, 2018)
Mobile robot's ability to maintain its speed is very important. When the robot is running and there is disturbance from outside system that affect the robot, causing the speed of the robot becomes unstable. For it is necessary to add a mechanism that is able to make the robot keep pace, one of them by giving control. This research will be built a speed control system on a mobile robot. The speed control system aims to improve performance and stability robot speed by minimizing the effect of unmeasured disturbances from outside the robot eg mechanical changes such as granting a load that can cause changes in the behavior of the system so that the necessary arrangements back to the control system. In this control system used control Proportional, Integral, Derivative (PID) and the analysis of disturbance based Disturbance Observer (DOB). PID control functions to improve motor performance robot. While DOB functions to analyze the disturbance from outside robot. The results of the implementation of the Disturbance Observer to PID control produce average root mean square error value of the reference value for the speed of 19.59 rpsfor right motor and left motor is 16.66 rps. While the average root mean square error of the reference value with PID control without Disturbance Observer on the right motor is 24.47 rps and the left motor is 18.89 rps. Keywords :